The development of an instructional model to promote Chinese reading and writing skills for university students - Luo, Menglan; Chano, Jiraporn; Chittranun, Thatchai; Shu, Yaping; Nithideechaiwarachok, Bussayarat (Frontiers in Education, 2023)
Because of the expanding global popularity of the language, more Thai colleges and universities have begun to offer Chinese language lessons in recent years. Yet, Thai teachers and students continue to struggle with how to teach and improve Chinese reading and writing skills. This research aimed to develop an instructional model based on second language acquisition theory to promote Chinese reading and writing skills for university students in the northeast of Thailand and study the results of the implementation. The participants were fifty second-year students majoring in Chinese from the faculty of humanities and social sciences of a public university. The instruments were an expert evaluation form, lesson plans, self-study reading quizzes, Chinese reading skills tests, a Chinese writing skills assessment form, and a questionnaire. Content analysis, mean, and also standard deviation were used to analyze the collected data. Thus, the findings revealed that the developed instructional model had the highest level of quality and appropriateness, which consisted of five components, including syntax and sequence, the social system, the principle of reaction, the support system, and the effect of the instructional model. The results of the implementation revealed that students' Chinese reading and writing skills had improved, and the student's attitudes toward learning with the developed instructional model were at a very high level. It is believed that this research could be beneficial for second-language Chinese students and teachers as well as other relevant parties involved in international Chinese education and research.